Prometheus reimagined : technology, environment, and law in the twenty-first century - Lin, Albert C. (The University of Michigan Press, 2013)
A call for a more thoughtful and democratic approach to technology policy and regulation.
Keywords: Technology -- Social aspects.; Technology -- Environmental aspects.; Technology and state.; Technology and law.; Technological innovations -- Law and legislation.; Science and state.; Technologie -- Aspect de l'environnement.; Politique scientifique et technique.; Technologie et droit.; Science and state; Technological innovations -- Law and legislation; Technology and law; Technology and state; Technology -- Environmental aspects; Technology -- Social aspects; LAW -- Science & Technology.